Family physicians overestimate diagnosis probabilities regardless of the test results - Ataç, Ömer; Küçükali, Hüseyin; Farımaz, Ayşe Zülal Tokaç; Palteki, Ayşe Seval; Çavdar, Sabanur; Aslan, Melek Nur; Atak, Muhammed; Sezerol, Mehmet Akif; Taşçı, Yusuf; Hayran, Osman (Frontiers in Medicine, 2024)
Introduction: As useful tools for clinical decision-making, diagnostic tests require careful interpretation in order to prevent underdiagnosis, overdiagnosis or misdiagnosis. The aim of this study was to explore primary care practitioners' understanding and interpretation of the probability of disease before and after test results for six common clinical scenarios.Methods: This cross-sectional study was conducted with 414 family physicians who are working at primary care in Istanbul via face-to-face interviews held between November 2021 and March 2022. The participants were asked to estimate the probability of diagnosis in six clinical scenarios providedThis is a provisional file, not the final typeset article to them. Clinical scenarios were about three cancer screening cases (breast, cervical and colorectal), and three infectious disease cases (pneumonia, urinary tract infection, and COVID-19). For each scenario participants estimated the probability of the diagnosis before application of a diagnostic test, after a positive test result, and after a negative test result. Their estimates were compared with the true answers derived from relevant guidelines.Results: For all scenarios, physicians' estimates were significantly higher than the scientific evidence range. The minimum overestimation was positive test result for COVID-19 and maximum was pretest case for cervical cancer. In the hypothetical control question for prevalence and test accuracy, physicians estimated disease probability as 95.0% for a positive test result and 5.0% for a negative test result while the correct answers were 2.0% and 0%, respectively (p<0.001).Discussion: Comparing the scientific evidence, overestimation in all diagnostic scenarios, regardless of if the disease is an acute infection or a cancer, may indicate that the probabilistic approach is not conducted by the family physicians. To prevent inaccurate interpretation of the tests that may lead to incorrect or unnecessary treatments with adverse consequences, evidence-based decision-making capacity must be strengthened.